Association of Sharing Materials with Pediculosis Capitis in Students of Pondok Pesantren Tahfidzil Qur’an Yayasan Tijarotal Lan Tabur Palembang - Dewi Arsinta; Chairil Anwar; Muhaimin Ramdja (Fakultas Kedokteran Universitas Sriwijaya, 2019)
Pediculosis capitis is a disease on human’s scalp andhair caused by infestation of Pediculus capitis. Transmission of pediculosis capitis can be through with direct contact between head-to-head and indirect contact from patient’s materials. The aim of this study was to determine the association of sharingmaterials with pediculosis capitis. This study was an analytic-observational study using a cross-sectionaldesign which was done in November 2018. This research was conducted on studentswho live at Pondok Pesantren Tahfidzil Qur’an Yayasan Tijarotal Lan Tabur Palembang. The sampleconsisted of 117 students. Data was collected through questionnaires and directobservation from hair sample. The results were analyzed using Chi-Square, Fisher’s Exact Testand Cox Regression.The study showed that prevalance of pediculosis capitis was 48.7%. From statistical analysis there was significant relationship between shared use of beds (p=0.039), combs (p=0.012), towels (p=0.046), veils (p=0.009) and caps (p=0.021) with the occurrence of pediculosis capitis. The multivariate test results using cox regression analysis showed that there was no dominant variables that influence incidence of pediculosis capitis on female students, while on the male students the most dominant variable was the shared use of towels (p=0.032) and caps (p=0.043) with variables shared use of caps as a predictor. There was significant association between the shared use of beds, combs, towels, veils and caps with the with pediculosis capitis, and the dominant variables on male student was shared use of caps.